Citizens' perceptions of police in rural US communities: a multilevel analysis of contextual, organisational and individual predictors - Holmes, Malcolm D. (Policing and society, 2017)
There has been little research on citizens' attitudes about policing in rural communities in the USA, and existing studies do not examine the effects of community characteristics on these attitudes. We extend this work theoretically and analytically by considering the effects of community context, police organisation and individual characteristics on attitudes about police. Using data for a large sample of citizens residing in 98 small towns in Iowa, we employed multilevel ordered logistic regression techniques to model citizens' rating of police protection and degree of trust in the police. At the community level, social disorganisation was negatively associated with both outcome variables, and social integration was positively related to trust in the police. Town police departments were viewed more favourably than county sheriff's offices for both police protection and trust. Individual-level perceptions of social integration and community safety were positively related to both outcome variables. Respondents' sociodemographic characteristics had relatively few significant effects. A statistical interaction between social disorganisation and individual perceptions of social integration was observed for trust in the police, with higher levels of perceived social integration attenuating the negative effect of social disorganisation. In sum, contextual, organisational and individual predictors all had important effects on attitudes about police in this study. These findings demonstrate that theories emphasising community context are essential to a more complete understanding of crime-related attitudes in rural communities.